MIMO Repetitive Control of an Active Magnetic Bearing Spindle. Issue 21 (2016) - Rai, Sandeep; Cavalier, Grant; Simonelli, James; Tsao, Tsu-Chin
Abstract: We present the identification and control of an open loop unstable MIMO Active Magnetic Bearing Spindle (AMBS) for machining applications. A 20th order model is obtained from reducing a higher order model identified by the ARX method. For verification purposes, the model is compared to the system's frequency responses obtained by the frequency sweep method. The model is used to design a linear quadratic optimal controller, where the weighting gains are tuned by simulation and experiment. A plug-in repetitive controller for asymptotic regulation and tracking of signals synchronous to the spindle rotation is designed by formulating the control design as a model matching filter design problem. The model matching's optimal solutions for the non-minimum phase MIMO stabilized system are obtained respectively for H ∞ and H 2 norm minimizations. Simulation and experimental results are presented to compare the proposed MIMO repetitive control design methods and demonstrate the control performance.